Letter from D. A. de Lima to James Curtis Booth - de Lima, D. A. (1876)
D. A. de Lima writes to James Curtis Booth (1810-1888) concerning gold bars.
Keywords: Booth, James Curtis, 1810-1888; Gold ingots; United States Mint; Mint of the United States